Investigation of core endurance, performance and functional activities in crossfit participants - Yentur, Songul Baglan; Elbasti, Muhammet Sahin; Kanan, Nesih; Boyrazli, Irem Sila (Elsevier, 2025)
Purpose Crossfit is a high-intensity and high-comprehensive continuously changing strength and conditioning program that has risk of injury. Core muscles are important for the protective mechanism of the spine and extremities. The aim of this study was to investigate core endurance, performance and functional activities in Crossfit participants. Methods The study included 20 crossfit participants, 20 fitness participants who had been participating in sports for at least 6 months and 20 physically inactive individuals. The McGill Tordo Endurance Test Battery was used to assess core endurance, the Functional Movement Screen test was used to assess function, and the 30-m sprint test, 3-min step test, vertical jump test, and one leg forward jump test were used to assess performance. Physical activity level was evaluated with International Physical Activity Questionnaire (IPAQ). Results Significant differences were observed between the groups in age, occupational status, and smoking status (p < 0.05). No significant differences were observed between the groups in height, weight, body mass index, gender and dominant extremity (p > 0.05). In addition, there were significant differences between the three groups in physical activity level, core endurance and performance tests (p < 0.05). In functional movement screen evaluation, no significant difference was obtained in deep squatting and shoulder mobility (p > 0.05), while significant differences were obtained among other parameters (p < 0.05). Conclusion Crossfit participants were found better core endurance, performance, function and physical activity levels than fitness participants and sedentary individuals.
Keywords: Crossfit training; Core endurance; Performance; Function